-(-x-3)=-(3x-12)

Simple and best practice solution for -(-x-3)=-(3x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-x-3)=-(3x-12) equation:



-(-x-3)=-(3x-12)
We move all terms to the left:
-(-x-3)-(-(3x-12))=0
We add all the numbers together, and all the variables
-(-1x-3)-(-(3x-12))=0
We get rid of parentheses
1x-(-(3x-12))+3=0
We calculate terms in parentheses: -(-(3x-12)), so:
-(3x-12)
We get rid of parentheses
-3x+12
Back to the equation:
-(-3x+12)
We add all the numbers together, and all the variables
x-(-3x+12)+3=0
We get rid of parentheses
x+3x-12+3=0
We add all the numbers together, and all the variables
4x-9=0
We move all terms containing x to the left, all other terms to the right
4x=9
x=9/4
x=2+1/4

See similar equations:

| -x-2=-2(-2x+6) | | 36=3/5x+18 | | -2(-x+6)=-x+12 | | X+162/18=x+120/15 | | (x+8)3=525 | | 3(3x-3)=x+4 | | 106+2x-10°=180 | | 13=m+2.1 | | -2(x-3)=-3x+6 | | -2(-x+6)=-3x-2 | | 8x^2=546 | | 6p+6p=-12 | | 3x+40=3(4x+3)+4 | | 10x^2=-90 | | 6x+3x-9=4 | | 14t−5t=18 | | -9=1+6x+2 | | 2/2-x+6/x2-x-2=1 | | -5x+37=14x+68 | | Y=8z+50 | | 2k+k=3 | | 3x+41=5(4x-3)+5 | | -2×-2(x+27)=-26 | | 8x+(5x-6-4x+1)=x-(x–4) | | -5x-26=4(2x-5)+7 | | -8x-4=-2+x-6-8× | | 1/3x+40=58 | | 3+k/2=k | | 7x+3=15+4x | | x=5=-1 | | 74-x+x=18 | | 4x+30=2x-30 |

Equations solver categories